Get to the end : a Catholic's view of the end times - Hickey, Michael (University Press of America, 2016)
A Catholic layman who views himself as uniquely "in the world," but not "of the world" provides a broader perspective on the "end times." This book is the first of its kind, a Catholic perspective that is not heavily weighed down in doctrine and dogma.